Spatial Owner-Dog Seroprevalence of Leptospira spp. Antibodies in Oceanic Islands and Costal Mainland of Southern Brazil - Freitas, Aaronson Ramathan; Delai, Ruana Renostro; Kmetiuk, Louise Bach; Gaspar, Raquel Cuba [UNESP]; da Silva, Evelyn Cristine [UNESP]; Martini, Rafaella; Biondo, Leandro Meneguelli; Giuffrida, Rogério; de Barros Filho, Ivan Roque; Santarém, Vamilton Alvares; Langoni, Helio [UNESP]; Pimpão, Cláudia Turra; et al. (MDPI, 2023)
Leptospirosis has been described as a disease neglected worldwide. Affecting humans and animals, the disease is often related to poor environmental conditions such as lack of sanitation and presence of synanthropic rodents. Despite being considered as a One Health issue, no study has focused on comparing owner–dog seroprevalence between islands and seashore mainland. Accordingly, the present study assessed anti-Leptospira spp. antibodies by applying microscopic agglutination test (MAT) methods to Leptospira and assessing associated risk factors via univariate and multivariate logistic regression analysis of owners and their dogs in islands and seashore mainland of southern Brazil. No anti-Leptospira spp. Seropositivity was found in 330 owner serum samples, while dogs presented an overall seroprevalence of 5.9%. All seropositive dogs reacted to serogroups of Leptospira interrogans, including 66.7% of Pyrogenes, 44.4% Canicola, 22.2% Icterohaemorrhagiae, 16.7% Australis; six reacted to more than one serogroup. No association was found among seropositivity and epidemiological variables, except that neighborhood dogs were less likely to be seropositive. Although no seropositivity was observed in owners, seropositivity in dogs had the potential to indicate such species as being sentinels for environmental exposure and potential human risk of infection.
Keywords: Brazil; domestic animals health; human health; leptospirosis; one health; seroepidemiology; zoonosis